Identitetna politika na univerzi - Močnik, Rastko (Slavistična revija, 2019)
The article analyzes the decision of the Senate of the Faculty of Arts (Ljubljana) concerning the "gender sensitive use of language." It concludes that the decision, while failing to fight discrimination against women, subverts the abstract universalism of revolutionary bourgeois law and promotes identity mechanisms that reproduce contemporary capitalism.
Keywords: contemporary capitalism; gender; govor; identitetna politika; identity politics; Slovenian language; slovenščina; sodobni kapitalizem; speech; spol